2021
DOI: 10.1080/21655979.2021.1936816
|View full text |Cite
|
Sign up to set email alerts
|

Screening of key biomarkers and immune infiltration in Pulmonary Arterial Hypertension via integrated bioinformatics analysis

Abstract: This study aimed to screen key biomarkers and investigate immune infiltration in pulmonary arterial hypertension (PAH) based on integrated bioinformatics analysis. The Gene Expression Omnibus (GEO) database was used to download three mRNA expression profiles comprising 91 PAH lung specimens and 49 normal lung specimens. Three mRNA expression datasets were combined, and differentially expressed genes (DEGs) were obtained. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, it has been found that the pathological process of PAH can lead to an increased ubiquitin-proteasome system- (UPS-) mediated muscle protein degradation and mitochondrial abnormalities, which in turn cause extensive abnormalities in skeletal and respiratory muscles of PAH patients, ultimately causing PAH-related restriction of motor function [ 47 ]. Previous studies have reported that NF- κ B can regulate gene expression and then be involved in many biological processes, such as inflammatory factor production, cell proliferation, effector cell survival, and differentiation, and that the NF- κ B signaling pathway is aberrantly activated in PAH models [ 48 , 49 ]. The new anesthetic sevoflurane can downregulate the levels of p-I κ B, p-P65, and P65 to inhibit NF- κ B signaling pathway activation in PAH rat models, thereby reducing lung fibrosis and ultimately preventing PAH [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that the pathological process of PAH can lead to an increased ubiquitin-proteasome system- (UPS-) mediated muscle protein degradation and mitochondrial abnormalities, which in turn cause extensive abnormalities in skeletal and respiratory muscles of PAH patients, ultimately causing PAH-related restriction of motor function [ 47 ]. Previous studies have reported that NF- κ B can regulate gene expression and then be involved in many biological processes, such as inflammatory factor production, cell proliferation, effector cell survival, and differentiation, and that the NF- κ B signaling pathway is aberrantly activated in PAH models [ 48 , 49 ]. The new anesthetic sevoflurane can downregulate the levels of p-I κ B, p-P65, and P65 to inhibit NF- κ B signaling pathway activation in PAH rat models, thereby reducing lung fibrosis and ultimately preventing PAH [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies apply machine learning methods to simulate the progression of malignancy and find significant characteristics that are then used in a categorization scheme. According to the results of our study and those of other researchers [50][51][52][53][54][55][56], this was the first study in which analytical methods for identifying PAH biomarkers use many machine learning approaches, including RF, Lasso, SVM-RFE, and WGCNA. Akter et al [57] suggest that merging different machine learning algorithms may boost prediction performance and construct highly accurate diagnostic models.…”
Section: Discussionmentioning
confidence: 63%
“…From a broad perspective, the development of PDS for clinical application is of great significance. Previous studies have examined key genes by DEG analysis between PAH lung specimens and normal lung specimens solely based on the public database in the GEO (27)(28)(29). The presence of heterogeneity of the disease and confounding factors reduces the sensitivity and specificity of DEGs as biomarkers for PAH.…”
Section: Discussionmentioning
confidence: 99%